Principles of regional self-government according to Council of Europe reference framework for regional democracy - Sakhanienko, Sierhiei; Kolisnichenko, Natalia; Drobot, Ihor (Pressing Problems of Public Administration, 2022)
The purpose of the article is to determine the general principles of regional self-government in accordance with the Framework recommendations of the Council of Europe on regional democracy. Ingenerak, this paper is intended to the content of Council of Europe Reference Framework for Regional Democracy, which in general form contains European standards of regional self-government, is examined. For a more complete presentation of the Reference Framework, the regulative acts of the Council of Europe relating to regional self-government were studied. The Reference Framework is presented as a means of transcending the scope of the European Charter of Local Self-Government in order to help governments strike the best possible balance in the apportionment of powers and responsibilities among different tiers of government. The Reference Framework is also analyzed on the basis of the principle of subsidiarity, the principle of social and territorial cohesion and the need for solidarity. The nature and principles of regional democracy are revealed. The characteristics of local and regional authorities which reflect the key principles of democracy and public participation in the management of living environments are examined. It is concluded that the essence of the principles of democracy constitute the combination of all principles and «rules for living» within a state. A comparison of the European standards of regional self-government with the regulatory practice of self-government functioning at the level of the regions of Ukraine has been carried out. The author’s vision on the introduction of regional self-government in Ukraine is presented.